TINGKAT ADOPSI PENGGUNAAN PUPUK HAYATI PADA BUDIDAYA PADI SAWAH (Oryza sativa L.) DI KECAMATAN BUNGURSARI KOTA TASIKMALAYA - Rafi Udin Rafiudin; Siswoyo Siswoyo; Ait Maryani (Universitas Sebelas Maret, 2022)
In lowland rice cultivation, farmers use chemical fertilizers without paying attention to the impact. If chemical fertilizers are not balanced with biological fertilizers, the organic content at paddy fields will decrease. This study aims to analyze the level of adoption, the factors that influence the adoption, and the strategies to increase the adoption of using biological fertilizers. This research was held in the Villages of Sukajaya, Sukamulya, and Sukarindik, Bungursari district, Tasikmalaya City, from April to June 2021. The research samples consisted of 71 farmers who were members of farmer groups. The samples were determined by using slovin’s formula. The variables of this study consist of internal factors, external factors, characteristics of innovation, and the level of adoption. Primary data was collected in the questionnaire form. The data was processed using descriptive analysis, multiple linear regression analysis, and SWOT analysis. The results of the study regarding the level of adoption of the use of biological fertilizers were in the medium category with a percentage of 49.3%. Factors that influence the level of adoption of biological fertilizers were formal education with a value of 0.026 <0.05, the relative advantage with a value of 0.001 <0.05, and the complexity with a value of 0.001 <0.05. The strategy to increase adoption using the SO strategy by maximizing to take advantage of farmer groups’ opportunities. For example, maximizing guidance to farmers through outreach activities to increase the use of biofertilizers and demonstrations on how to make biofertilizers.